THE EFFECTIVENESS OF ANIMATION VIDEOS IN IMPROVING STUDENTS’ SPEAKING SKILL - Anwar Musadad; Setya Resmini (PROJECT (Professional Journal of English Education), 2024)
In this school from home period, teachers should provide creative methods or medias to make students engage with the learning activity. One of the medias that teachers can be use is by using animation videos. The objective of this research is to discover whether animation videos could improve students’ speaking skill or not. The subject of this research was 29 of high school students in Cianjur. The researchers used SPSS to analyzed the data. The researcher guided by the following hypothesis: Null hypothesis (H0): animation videos can not improve students' speaking skills. Alternative hypothesis: animation videos can improve students’ speaking skills. Based on the test results, the mean of pre-test score is 62.38, and the mean of post-test 74.46, which showed a significant improvement toward student’ speaking skill. In conclusion, animation videos can improve students’ speaking skill.